ANALYSIS OF THE MEANING OF 'LAA ILAAHA ILLALLAH' AND THE URGENCY OF TAUḤĪD EDUCATION IN THE LIFE OF MUSLIMS - Yasin, Hadi (Tahdzib Al-Akhlaq: Jurnal Pendidikan Islam, 2025)
This article examines the significance of Lā ilāha illallāh (“There is no god but Allah”) and the importance of tawḥīd education in the lives of Muslims. As the theological foundation of Islam, the testimony of divine unity holds profound significance not only as a verbal statement but also as a transformative paradigm shaping belief, ethics, and education. The study employs a qualitative approach with descriptive-analytical methods, examining classical Islamic sources, Qur’anic and Hadith evidence, and contemporary scholarship from national and international journals, including Scopus-indexed publications. The findings indicate that Lā ilāha illallāh is characterized by dual aspects: negation (nafy) of all false deities and affirmation (ithbāt) of God’s sole divinity. Classical scholars such as Ibn Taymiyyah, al-Ghazālī, and Ibn Qayyim emphasize that the testimony requires both internal conviction and external practice, encompassing sincerity, certainty, and ethical obedience. Modern studies expand this framework by linking monotheism to contemporary challenges such as secularism, moral relativism, and technological ethics. In the Indonesian context, research demonstrates a gap between cognitive understanding of tawḥīd and its practical application in everyday life, especially among students exposed to globalization and digital culture. This study concludes that tawḥīd education must be re-centered as the axis of Islamic pedagogy. By integrating classical wisdom and modern realities, Lā ilāha illallāh can function as both a theological creed and an educational strategy, fostering intellectual coherence, spiritual resilience, and ethical clarity in Muslim identity formation.